Facilitating teachers' professional growth through their involvement in creating context-based materials in science - George, June M; Lubben, Fred (International Journal of Educational Development, 2002)
This paper traces the professional growth of science teachers in Trinidad and Tobago through their involvement in the production of context-based resource materials relevant to the lives of their students during workshop sessions. Grounded theory methods were used to analyse pre- and post-workshop questionnaire responses, tape-recorded group discussions and several draft lesson outlines. The findings show that professional growth is indicated by changes in the nature of the contexts chosen as lesson foci, the role of these contexts in the overall lesson design, and teachers' perceptions of contextualised teaching. Conflicts between students' cultural and scientific understandings were not addressed by these teachers.
Keywords: Contextualisation; International education; Professional development; Science Teachers; curriculum materials